Peran Sosialisasi dan Edukasi Masyarakat dalam Menumbuhkan Minat Investasi Digital - Karula Yuan Maharani; Hesty Prima Rini (Politeknik Kampar, 2023)
Digital investment has become an increasingly important topic in today's digital era, however, there are still many people who do not understand the concept and benefits of digital investment, and do not have enough interest to be involved in it. The phenomenon of many people who do not understand the concept and benefits of digital investment is also found around PT Victory International Futures which is an official brokerage company or broker that has been supervised by Bappebti. Through community service activities with socialization methods, the author aims to increase public understanding and interest in digital investment. The results of this service activity show that public socialization and education have a significant role in increasing interest in digital investment, with the understanding provided can reduce the negative stigma and fear felt by the community about investment and help people to manage finances and take advantage of economic opportunities through investment.